Physicochemical Changes of Repeatedly Used Oils for Food Frying Collected From Some Restaurants in Sudan - Shakak, Mahdi Abbas Saad; Okasha, Kholoud Reda Aldeen Awad; Mustafa, Salma Elgali (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
This research was conducted to study the effect of repeated use of frying oil on physicochemical properties of cottonseed oil and sunflower oil as common edible oils used for food frying in Sudan (check pea (tammiya) , potato chips and fish ) . Samples were collected randomly from different restaurants in Khartoum State for three days in the morning and evening, then the following tests were carried out (viscosity, refractive index, colour, smoking point, free fatty acid, polymer content, peroxide value and iodine value) All physical properties (viscosity, smoking point, and colour) of the collected cottonseed and sunflower oils used for frying check pea, potato chips and fish during the morning were significantly different from those collected samples of the same products during evening from the same restaurants. Also it was noticed that all chemical properties which were carried out (iodine value, polymer content, peroxide value and free fatty acids) of the collected cottonseed oil and sunflower oils used for frying check pea, potato chips and fish during the morning were significantly different from those collected samples of the same products during evening from the same restaurants located in Khartoum State. It was concluded that all the collected samples of the used oils were deteriorated and should be discarded.